UVEAL METASTASIS BASED ON PATIENT AGE IN 1, 111 PATIENTS: Comparison of Clinical Features and Outcomes Per Age Category. Issue 2 (February 2020) - Shields, Carol L.; Acaba-Berrocal, Luis A.; Selzer, Evan B.; Mayro, Eileen L.; Newman, Jennifer H.; Malik, Kunal; Welch, R. Joel; Shields, Jerry A.
Abstract : Purpose: To evaluate clinical features and survival outcomes of uveal metastasis based on patient age. Methods: Retrospective analysis of all patients with uveal metastasis evaluated on the Ocular Oncology Service, Wills Eye Hospital, Philadelphia, PA, USA between February 1, 1974 and June 1, 2017. The features and outcomes were analyzed based on patient age classified as children (0–20 years), young adults (21–40 years), middle [aged] adults (41–60 years), older adults (61–80 years) and senior adults (81–100 years). Results: There were 1111 consecutive patients, including children (n = 3, <1%), young adults (n = 77, 7%), middle adults (n = 472, 42%), older adults (n = 509, 46%), and senior adults (n = 50, 4%). At uveal metastasis diagnosis, demographics included mean patient age of 60 years, Caucasian race (88%), and female gender (64%). Compared to the largest cohort (older adults), there were significant differences (age group versus [vs.] older adults) in Caucasian race (senior adult 98% vs. 89%, p = 0.042), male sex (young adults: 22% vs. 43%, p < 0.001) (middle adults: 29% vs. 43%, p < 0.001), unilateral tumor (young adult: 70% vs. 86%, p < 0.001) (middle adult: 79% vs. 86%, p = 0.003) (senior adults: 96% vs. 86%, p = 0.045), and cancer origin in breast (young adults: 51% vs. 32%, p = 0.002) (middle adults: 44% vs 32%, p < 0.001), lung (young adults: 14% vs. 30%, p = 0.004), kidney (young adults: 0% vs. 5%, p = 0.043), prostate (middle adults: 1% vs. 4%, p = 0.001), gastrointestinal tract (senior adults: 8% vs. 2%, p = 0.028), and others (children: 100% vs. 4%, p < 0.001) (young adults: 10% vs. 4%, p = 0.044). Kaplan-Meier survival (children, young, middle, older, and senior adults) at 1 year was 33%, 48%, 60%, 62%, and 76% and at 5 years was 0%, 22%, 29%, 25%, and 40%, respectively, with no difference per age category. The mean overall survival was 17.2 months and children demonstrated hazard ratio (HR) for death at 1 year of 2.1 relative to older adults. Conclusion: Uveal metastasis is found in all age groups. Compared to older adults, primary cancer site was more often breast and less likely lung in young and middle adults. Other rare sites were more often seen in children. Survival outcomes at 1 and 5 years were most favorable for senior adults and least favorable for children. Abstract : A review of 1, 111 patients with uveal metastasis revealed that cancer origin in breast was more common in young- and middle-aged adults and in lung, kidney, and prostate in senior adults. Children with uveal metastasis fared poorly with hazard ratio for death at 1 year of 2.1 compared with older adults.